2038. Invasive Mucormycosis Management: Mucorales PCR Provides Important, Novel Diagnostic Information. (26th November 2018) - Wilgers, Kyle; Waddell, Joel; Tyler, Aaron; Altrich, Michelle; Hays, Allyson; Kleiboeker, Steve; Yin, Dwight; Wissel, Mark
Abstract: Background: In immunocompromised patients, high mortality and morbidity of invasive mucormycosis (IM) remain significant healthcare issues due in part to confusion of IM with invasive aspergillosis (IA) and failure to initiate appropriate therapy. A validated Mucorales (MUC) PCR detects the causative agents of IM with good sensitivity and specificity, as reported previously (M-227, ICAAC 2013). Published studies have not definitively determined the frequency of patients for whom pulmonary IA is suspected but IM is present. We aimed to (1) estimate the frequency of MUC PCR positivity in bronchoalveolar lavage (BAL) samples submitted for Aspergillus (ASP) PCR panel testing. Methods: We identified 1, 067 clinical BAL specimens originally submitted to a reference laboratory for ASP PCR panel testing. Eluates from DNA extraction were tested by MUC PCR, which detects known pathogens from seven Mucorales genera ( Apophysomyces, Cunninghamella, Lichtheimia [previously Absidia], Mucor, Rhizomucor, Rhizopus and Saksenaea ). Results: The proportions of MUC PCR and ASP PCR positive BAL specimens were 1.5% (16) and 6.9% (74), respectively. 87.5% (14/16) of the MUC positive (POS) were ASP negative (NEG). One patient had two MUC PCR POS BAL samples within the testing period. The MUC quantification averaged 20, 000 copies per mL BAL (range 24–266, 000), which is >1, 000-fold above the assay the 20 copies/mL limit of detection (LOD). Two of the ASP POS's were MUC POS ( 400 and 20-fold above LOD). For patients with MUC POS BALs, physicians requested on average 6.3 pneumonia-related tests (e.g., ASP PCR, Galactomannan, Legionella PCR, etc.) within 2 weeks of the tested BAL. In total 94.0% (85/91) of these orders yielded NEG results. The MUC PCR was physician-ordered in only one (6.25%) of the MUC POS BALs. Conclusion: In BAL samples submitted for IA testing, 16 cases (1.5%) had POS MUC PCR. The observed 5:1 (ASP:MUC) ratio approximates published literature on invasive mould incidence. MUC POS concurrent with NEG results for other pathogens suggest potential missed opportunities for MUC early diagnosis and treatment in cases of suspected invasive mould. Disclosures: K. Wilgers, Viracor Eurofins Clinical Diagnostics: Employee, Salary. J. Waddell, Viracor-Eurofins: Collaborator, No financial benefit. A. Tyler, Viracor Eurofins Clinical Diagnostics: Employee, Salary. M. Altrich, Viracor Eurofins Clinical Diagnostics: Employee, Salary. S. Kleiboeker, Viracor Eurofins Clinical Diagnostics: Employee, Salary. D. Yin, Viracor-Eurofins: Collaborator, No financial benefit. ; Marion Merrell Dow Fund: Grant Investigator, Research grant. ; Astellas: Investigator, Research grant. ; Merck: Investigator, Research grant. M. Wissel, Viracor Eurofins Clinical Diagnostics: Employee, Salary.